Quantification of morning stiffness to assess disease activity and treatment effects in rheumatoid arthritis. (5th April 2021) - Boeth, Heide; Biesen, Robert; Hollnagel, Jeremias; Herrmann, Sandra; Ehrig, Rainald M; Pelli, Lorenzo; Taylor, William R; Duda, Georg N; Buttgereit, Frank
Abstract: Objectives: The clinical parameter of morning stiffness is widely used to assess the status of RA, but its accurate quantitative assessment in a clinical setting has not yet been successful. This lack of individual quantification limits both personalized medication and efficacy evaluation in the treatment of RA. Methods: We developed a novel technology to assess passive resistance of the MCP III joint (stiffness) and its passive range of motion (PRoM). Within this pilot study, 19 female postmenopausal RA patients and 9 healthy controls were examined in the evening as well as the morning of the following day. To verify the specificity of the biomechanical quantification, 11 patients with RA were assessed both prior to and ∼3 h after glucocorticoid therapy. Results: While the healthy controls showed only minor changes between afternoon and morning, in RA patients the mean PRoM decreased significantly by 18% (s .d . 22) and stiffness increased significantly by 20% (s .d . 18) in the morning compared with the previous afternoon. We found a significant positive correlation between RA activity and biomechanical measures. Glucocorticoids significantly increased the mean PRoM by 16% (s .d . 11) and reduced the mean stiffness by 23% (s .d . 22). Conclusion: This technology allowed mechanical stiffness to be quantified in MCP joints and demonstrated high sensitivity with respect to disease status as well as medication effect in RA patients. Such non-invasive, low-risk and rapid assessment of biomechanical joint stiffness opens a novel avenue for judging therapy efficacy in patients with RA and potentially also in other non-RA inflammatory joint diseases.